2016
DOI: 10.1155/2016/9276508
|View full text |Cite
|
Sign up to set email alerts
|

A Virtual Reality-Cycling Training System for Lower Limb Balance Improvement

Abstract: Stroke survivors might lose their walking and balancing abilities, but many studies pointed out that cycling is an effective means for lower limb rehabilitation. However, during cycle training, the unaffected limb tends to compensate for the affected one, which resulted in suboptimal rehabilitation. To address this issue, we present a Virtual Reality-Cycling Training System (VRCTS), which senses the cycling force and speed in real-time, analyzes the acquired data to produce feedback to patients with a controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 39 publications
0
16
0
1
Order By: Relevance
“…VR represents a promising technology that, in the near future, can be easily become part of different rehabilitation treatments, as demonstrated by the great number of studies reported in literature [ 36 , 43 , 58 , 59 ]. However, before its introduction in the clinical practice, it is necessary to consider both the pathology-related complications that potential users may have and the usability aspect of the designed system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VR represents a promising technology that, in the near future, can be easily become part of different rehabilitation treatments, as demonstrated by the great number of studies reported in literature [ 36 , 43 , 58 , 59 ]. However, before its introduction in the clinical practice, it is necessary to consider both the pathology-related complications that potential users may have and the usability aspect of the designed system.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies already adopted a VR cycling training for the motor rehabilitation of old adults or stroke patients [ 43 , 44 , 45 , 46 , 47 ], but no one ever implemented it into a DT protocol, thus requiring the execution of some interactive cognitive tasks during the physical performance of the virtual ride. To our knowledge, studies exploiting VR-based dual task training focused on exercises requiring locomotion and involved either the use of a treadmill [ 48 , 49 ] or implemented stepping-in-place on a balance board [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…For a post-stroke patient that suffers from severe lower limb muscle weakness and cannot participate in a gait training session in a safe manner, the movement training in the sitting position is preferred. It is found that the outcomes of the training in sitting position can reduce motor impairments and translate to into improved walking ability [10,11,18]. The lower limb rehabilitation robot in our research is developed to provide physical therapy to the patient with this stage.…”
Section: Robot Descriptionmentioning
confidence: 99%
“…Furthermore, various training modalities and activities can be selected to suit with the condition of the patient [3,7]. The robots can also be implemented with games and virtual reality systems to motivate the patient to actively participate in the training session [8][9][10]. Table 1 shows clinical results from trainings with games and virtual reality systems implemented by lower limb rehabilitation robots, namely, Rutgers Ankle [11], Anklebot [12], VRCTS [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation